Investigation of Quality of Life of Patients with Atopic Dermatitis and Quality of Life, Psychiatric Symptomatology, and Caregiver Burden of Their Mothers - Nülüfer Kilic; Mehmet Kilic (MDPI AG, 2023)
Background: The purpose of the present research was to evaluate the quality of life of patients with atopic dermatitis (AD), and that of their mothers. We compared the anxiety and depression scores and caregiving burden of mothers of patients with AD with the same scores of mothers of healthy children. Materials and Methods: A total of 153 patients between the ages of 2 months and 16 years with AD in our clinic, and their mothers, were contained in the patient group. An additional 141 healthy cases between the ages of 2 months and 16 years, and their mothers, were included as the control group. The Children's Dermatology Life Quality Index (CDLQI) was completed according to the children's opinions, and the Infant's Dermatitis Quality of Life Index (IDLQI), Family Dermatology Life Quality Index (FDLQI), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Temperament Evaluation of Memphis, Pisa, Paris and San Diego Autoquestionnaire, and Zarit Caregiver Burden (ZCB) scale were completed based on the mothers' opinions. Results: We detected a positive relationship between the SCORAD index and the IDLQI, CDLQI, and FDLQI scores of children with AD. We found that anxiety, depression, and caregiving burden in mothers of AD cases increased when mothers of AD cases were compared with mothers of healthy children (p < 0.0001, p < 0.0001, and p < 0.002, respectively). Also, based on the mothers' responses, we noted a positive correlation among the BDI, BAI, ZCB, and SCORAD index scores. Conclusions: Our study found that the quality of life of patients with AD, and that of their mothers, was negatively affected by the disease. We also found that anxiety, depression levels (not at the clinical diagnosis level, and the caregiving burden in mothers of AD cases increased when mothers of AD cases were compared with mothers of healthy children.